Chronic expression of interferon‐gamma leads to murine autoimmune cholangitis with a female predominance. Issue 4 (15th June 2016) - Bae, Heekyong R.; Leung, Patrick S.C.; Tsuneyama, Koichi; Valencia, Julio C.; Hodge, Deborah L.; Kim, Seohyun; Back, Tim; Karwan, Megan; Merchant, Anand S.; Baba, Nobuyuki; Feng, Dechun; Park, Ogyi; et al.
Abstract : In most autoimmune diseases the serologic hallmarks of disease precede clinical pathology by years. Therefore, the use of animal models in defining early disease events becomes critical. We took advantage of a "designer" mouse with dysregulation of interferon gamma (IFNγ) characterized by prolonged and chronic expression of IFNγ through deletion of the IFNγ 3′‐untranslated region adenylate uridylate‐rich element (ARE). The ARE‐Del ‐/‐ mice develop primary biliary cholangitis (PBC) with a female predominance that mimics human PBC that is characterized by up‐regulation of total bile acids, spontaneous production of anti‐mitochondrial antibodies, and portal duct inflammation. Transfer of CD4 T cells from ARE‐Del ‐/‐ to B6/Rag1 ‐/‐ mice induced moderate portal inflammation and parenchymal inflammation, and RNA sequencing of liver gene expression revealed that up‐regulated genes potentially define early stages of cholangitis. Interestingly, up‐regulated genes specifically overlap with the gene expression signature of biliary epithelial cells in PBC, implying that IFNγ may play a pathogenic role in biliary epithelial cells in the initiation stage of PBC. Moreover, differentially expressed genes in female mice have stronger type 1 and type 2 IFN signaling and lymphocyte‐mediated immune responses and thus may drive the female bias of the disease. Conclusion: Changes in IFNγ expression are critical for the pathogenesis of PBC. (Hepatology 2016;64:1189‐1201)